ANALISIS KESULITAN SISWA DALAM MEMBUAT TEKS PIDATO PADA SISWA KELAS VI SEKOLAH DASAR - Boby Waluyo Purna Irawan (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
This study aims to analyze the difficulties of students in writing speech texts. This research is a qualitative descriptive study. The method used is content analysis, where students' speeches are used as research data to find out what difficulties students feel. From the results of the general analysis on the elements of the speech text such as the opening, content, and closing. There were 7 students who scored below the KKM out of 20studentsand it was found that most of the difficulties experienced by students were in the aspect of expressing the essence of the problem as much as 70%, aspects of the relationship between information and topics as much as 50%, and aspects of writing conclusions as much as 45%.